Impact of 1-Methylcyclopropene combined with chitosan on postharvest quality of tropical banana ‘Lady Finger’ - Syariful Mubarok (International Journal of Food Properties, 2022)
‘Lady Finger’ banana is one of the most-produced bananas in Indonesia. Unfortunately, it has a short fruit shelf life, which became a major problem in post-harvest handling. Shelf life in climacteric fruits can be improved through the inhibition of physiological processes such as ethylene production, respiration, and transpiration by the application of 1-Methylcyclopropene (1-MCP) and chitosan. Physiological process inhibition will influence fruit color, firmness, sugar content, and other postharvest qualities. The potential use of 1-MCP, chitosan, and a combination of both toward postharvest life quality of ‘Lady Finger’ banana were assessed in this study. Four concentrations of 1-MCP (0.25, 0.50, 0.75, and 1.00 µL/L) and also its combination with 1.25% chitosan were applied to the ‘Lady Finger’ banana. The result showed that the combination of 1-MCP and chitosan improved the postharvest life quality of the ‘Lady Finger’ banana. The combination of 1-MCP (0.5–1.0 µL/L) and chitosan increased fruit shelf life up to 5–6 days longer compared to control and inhibited the change of fruit pH, TA, TSS, total sugar, color index, and weight loss. These results indicate that the effect of 1-MCP will be more effective in improving the fruit shelf life of bananas if it is combined with chitosan.